Pengaruh waktu tunggu, harga, dan kualitas pelayanan terhadap kepuasan konsumen pada maskapai XYZ Terminal 1B di Bandara Soekarno Hatta - Warsih, Seri (Jurnal Manajemen Bisnis dan Kewirausahaan, 2017)
This study aims to determine the effect of waiting time, price, and quality of service on customer satisfaction and analyze the most dominant variable affecting consumer satisfaction. The results of this study are expected to realize the management of companies more effectively and efficiently. The population in this research is all passengers who use flight service from XYZ terminal 1B at the Soekarno Hatta Airport Tangerang. The sampling technique conducted by the researcher is purposive sampling so in the study only 100 passengers using XYZ airline. Method of data collection using questionnaire method and data analysis method using quantitative analysis with hypothesis proof. Hypothesis testing conducted is a classical assumption test, multiple linear regression analysis, coefficient of determination (R2), “t” test, and “F” test. Based on the results of data analysis and hypothesis testing, it can be concluded as follows: 1) Waiting time is partially influential and significant to customer satisfaction; 2) Price is partially influential and significant to customer satisfaction; 3) Quality of service is partially influential and significant to customer satisfaction; and 4) Waiting time, price, and service quality simultaneously have an effect on and significant to consumer satisfaction.